2021
DOI: 10.3390/cells10061553
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-Glia-Immune Triad and Cortico-Limbic System in Pathology of Pain

Abstract: Pain is an unpleasant sensation that alerts one to the presence of obnoxious stimuli or sensations. These stimuli are transferred by sensory neurons to the dorsal root ganglia-spinal cord and finally to the brain. Glial cells in the peripheral nervous system, astrocytes in the brain, dorsal root ganglia, and immune cells all contribute to the development, maintenance, and resolution of pain. Both innate and adaptive immune responses modulate pain perception and behavior. Neutrophils, microglial, and T cell act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…Neutrophils infiltrate into the site of acute nerve injury and release nerve growth factor and chemokine. Chemokines containing C–X–C and C–C sequences recruit macrophages and monocytes from peripheral blood through CCR1, 2 and 5 to participate in the production of pain (Murray et al., 2021 ). After the activation of neurons, the upregulation of immune cell function genes in DRG can further promote the recruitment of macrophages and T cells and then secrete inflammatory factors to stimulate the continued activation of microglia (Malcangio, 2019 ; Murray et al., 2021 ).…”
Section: Results and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils infiltrate into the site of acute nerve injury and release nerve growth factor and chemokine. Chemokines containing C–X–C and C–C sequences recruit macrophages and monocytes from peripheral blood through CCR1, 2 and 5 to participate in the production of pain (Murray et al., 2021 ). After the activation of neurons, the upregulation of immune cell function genes in DRG can further promote the recruitment of macrophages and T cells and then secrete inflammatory factors to stimulate the continued activation of microglia (Malcangio, 2019 ; Murray et al., 2021 ).…”
Section: Results and Prospectsmentioning
confidence: 99%
“…Chemokines containing C–X–C and C–C sequences recruit macrophages and monocytes from peripheral blood through CCR1, 2 and 5 to participate in the production of pain (Murray et al., 2021 ). After the activation of neurons, the upregulation of immune cell function genes in DRG can further promote the recruitment of macrophages and T cells and then secrete inflammatory factors to stimulate the continued activation of microglia (Malcangio, 2019 ; Murray et al., 2021 ). In humans, the upregulation of TSPO (translocator protein) is often accompanied by the activation of glial cells.…”
Section: Results and Prospectsmentioning
confidence: 99%
“…The limbic cortex includes the allogenic cortex (such as the ancient cortex of the hippocampus and dentate gyrus, the septum and the amygdala, etc.) and the intermediate cortex (including the posterior part of the orbitofrontal cortex, insula, temporal pole, cingulate gyrus, etc.,), which participate in mediating instinctual and emotional behavior [ 42 ]. At the same time, neuroanatomy has confirmed that the prefrontal lobe is the key part of emotion regulation, which is related to cognition, emotion and conscious experience.…”
Section: Discussionmentioning
confidence: 99%
“…[49,50] Glia cells are modulators of pain sensation and spinal astrocytes are activated in response to a wide array of conditions, including inflammation and immune activation. [51,52] Activation of glial cells, production of inflammatory mediators, and infiltration of leukocytes are the main characteristic features of neuroinflammation. [53] We also observed infiltration of inflammatory cells and the activation of astrocytes in the spinal dorsal horn of OXA-treated rats represented by the increased expression of GFAP in the current study (Figure 2) which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%